Efeito da adição de ureia e Lactobacillus buchneri em silagens de milho - Santos, Ana Paula Maia dos (2018)
The objective of this study was to evaluate the effects of the addition of urea and Lactobacillus buchneri lyophilized and activated inoculant in reconstituted skim milk, by testing the effects of the isolated and associated additives on the fermentative characteristics, microbial populations and aerobic stability of corn silages. Two experimental trials were carried out in the Forage Sector of the Center of Agrarian Sciences, Campus II, Federal University of Paraíba. In the first experiment, the treatments evaluated were the addition levels of 0.0; 0.5; 1.0; 1.5 and 2.0% urea, based on the dry matter. In the second experiment, the silages were treated with lyophilized inoculant without and with urea, inoculant activated without and with urea, and 1% of urea, in different fermentation periods (1, 3, 7, 14 and 70 days). The fermentative variables evaluated were: pH, dry matter content, organic acids and ethanol, dry matter losses, gas and effluent losses, dry matter recovery, bromatological composition and lactic acid bacteria and yeast populations. The silages were exposed to air during the 96 hour period and pH values, yeast populations, maximum temperature reached by silages and aerobic stability were evaluated. After counting populations of lactic acid bacteria from the silages, polymerase chain reaction analysis was performed to identify the isolated bacteria. The addition of urea in the silages promoted improvements in the fermentation profile, reduction of losses, increase of nitrogen in the ensiled mass, reduction of the fibrous content and increase of the aerobic stability of corn silages. The inoculation of silages with lyophilized and activated strains did not present expressive results when carried out alone. The addition of Lactobacillus buchneri and urea in maize silage affected the fermentation profile, fermentative losses and aerobic stability, populations of lactic acid bacteria and yeasts and the bromatological composition of the silages. The aerobic stability of the silages treated with additives was higher than those not treated. The results of the analysis of identification of lactic bacteria isolated in the untreated and treated silages with lyophilized inoculant and activated in reconstituted skimmed milk did not indicate the predominance of Lactobacillus buchneri in the additive silages.